A comparison of plantar pressures between two different playing surfaces in tennis - Eckl, M.; Kornfeind, P.; Baca, A. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare two different playing surfaces in tennis - clay vs hard-court (OptiCourt) - in order get more insight on the influence of the effect of surface on load. Eight male tennis players performed two types of tennis specific motions. Inside plantar pressure was measured for the right foot during these movements. Higher maximum forces could be observed for the OptiCourt for the baseline play. In more detail, maximum force, peak and mean pressure were higher for the heel region on the hard-court. Higher values were found on clay for the hallux and lesser toe region. These results are in agreement with those of previous studies as they give evidence that playing surface affects loading in tennis.